2002
DOI: 10.1007/s004150200065
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of acute ischaemic stroke with the low-affinity, use-dependent NMDA antagonist AR-R15896AR

Abstract: In most of the patients with acute stroke receiving AR-R15896AR the intended high plasma levels were reached within a short time period. However, active treatment produced more side effects than placebo, thus indicating safety concerns and tolerability issues for use in high doses in an acute stroke population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…520, 521 The NMDA antagonist AR-R15896AR was tested in a clinical trial, but side effects, including psychiatric disturbances, meant that the agent could not be tolerated by the patient. 522 A preliminary study of the ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid antagonist ZK 200775 showed that the medication led to declines in consciousness and possible neurological worsening. Studies of the glycine antagonist gavestinel found that the medication was relatively safe, but the likelihood of favorable outcomes was not improved.…”
Section: Neuroprotective Agentsmentioning
confidence: 99%
“…520, 521 The NMDA antagonist AR-R15896AR was tested in a clinical trial, but side effects, including psychiatric disturbances, meant that the agent could not be tolerated by the patient. 522 A preliminary study of the ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid antagonist ZK 200775 showed that the medication led to declines in consciousness and possible neurological worsening. Studies of the glycine antagonist gavestinel found that the medication was relatively safe, but the likelihood of favorable outcomes was not improved.…”
Section: Neuroprotective Agentsmentioning
confidence: 99%
“…This receptor is known to have dual effects; it promotes neuronal death or survival in primary neuronal cultures in vitro and in the rat brain in vivo, depending on the level of receptor activity [69]. This may explain why in some clinical trials using a low-affinity blocker of the NMDA ion channel, mortality in patients with acute ischemic stroke was not reduced [70]. …”
Section: Perspective Therapiesmentioning
confidence: 99%
“…738 Several N-methyl-d-aspartate antagonists have been tested in clinical trials, with largely negative results and increased rates of serious adverse events. [739][740][741][742][743][744][745][746][747][748][749][750][751][752] A 2003 systematic review of the excitatory amino acid modulator trials found no rates of improvements in either death or favorable outcomes with treatment. 753 Lubeluzole, which is thought to downregulate the glutamate-activated nitric oxide synthase pathway, was tested in several clinical trials, including one that evaluated the combination of the medication and intravenous rtPA.…”
Section: Pharmacological Agentsmentioning
confidence: 99%